Evaluating chemiluminescent immunoassays for syphilis detection: A comparative analysis - Ahmed, Ismail (2025)
BackgroundSyphilis, caused by Treponema pallidum (TP), remains a significant global public health concern, with approximately 8 million new cases annually. Diagnosing syphilis is challenging due to its often-asymptomatic nature during latent stages, necessitating a combination of diagnostic methods. This study evaluates the performance of a novel chemiluminescent immunoassay (CLIA) developed by Mindray for detecting TP antibodies, comparing it to the widely used Abbott ARCHITECT Syphilis Treponemal Test (Architect-TP), the rapid plasma regain (RPR) test, and the Fujiribio INNO-LIA® Syphilis Score line immunoassay (INNO-LIA-TP). MethodsWe selected 180 samples that exhibited agreement or discrepancies between the RPR and Architect-TP assays. The selection included 40 cases that were RPR positive and Architect-TP positive, 40 cases that were RPR positive and Architect-TP negative, and 100 cases that were negative in both RPR and Architect-TP. All samples underwent re-testing using the Mindray-TP and INNO-LIA-TP assays. ResultsMindray-TP and Architect-TP exhibited excellent sensitivity of 100 % (95 % CI: 91–100) and specificity of 100 % (95 % CI: 97.4–100), with perfect agreement (κ= 1.00) compared to INNO-LIA-TP. Notably, 40 cases (28.6 %; 40/140) demonstrated false-positive results when using the RPR test compared to INNO-LIA-TP, indicating a substantial false-positive rate for the RPR assay. ConclusionThis study highlights the high diagnostic accuracy of the Mindray-TP assay, positioning it as a reliable and efficient tool for syphilis screening in high-volume laboratories. Given its operational efficiency and strong agreement with gold-standard assays, Mindray-TP can enhance diagnostic workflows, leading to timely syphilis detection and improved patient outcomes.